THE INFLUENCE OF ORGANIZATIONAL CHANGE ON PSYCHOSOCIAL AND ITS IMPACT ON ORGANIZATIONAL PERFORMANCE WITH LEADERSHIP AS A MODERATOR AT THE NORTH SUMATRA PROVINCE BKKBN REPRESENTATIVE - Eka Yulinda Prasetyowati; Isfenti Sadalia; Nazaruddin (RADJA PUBLIKA, 2024)
In facing very rapid changes in the strategic environment, the Indonesian Government needs dynamic, agile and adaptive governance management. To make this happen, a streamlined bureaucracy is needed so that strategic decisions can be made quickly and according to needs. So it is necessary to simplify the bureaucracy (delayering) which touches the root of the problem and changes the ASN mindset to encourage innovation. The simplification of bureaucracy has resulted in major changes to the ASN work system mechanism. These changes include: organizational structure, authority relationships, coordination mechanisms, job descriptions, span of control, employee work patterns. These changes have an impact on employee performance and organizational performance. The aim of this research is to analyze the factors that influence Employee Readiness for Change at the North Sumatra Province BKKBN Representative. Data analysis in this research uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS). This research measures the influence of Organizational Commitment, Employee Engagement, and Perceived Organizational Support on Employee Readiness for Change. The research results show that Organizational Commitment and Perceived Organizational Support have a significant effect on Readiness for Change. Meanwhile, Employee Engagement did not show a significant influence on Readiness for Change among North Sumatra Province BKKBN Representative employees. The R-Square value of the Readiness for Change (Y) variable is 0.894, which means that the variables Organizational Commitment (X1), Employee Engagement (X2) and Perceived Organizational Support (X3) are able to influence 89.4%, while the remaining 10.6% influenced by other variables not examined in this research.